Pengaruh Sekulerisme terhadap Ilmu Modern Saat Ini dan Langkah Mengatasinya dari Sudut Pandang Islam - Khamdani, Agus Walid; Mujib, Ahmad; Sumiran, Sumiran (TSAQOFAH, 2025)
This study examines the ideological influence of secularism on science and modern education, particularly its removal of spiritual and moral values from the scientific framework. The aim is to analyze the history, characteristics, and impacts of secularism in the context of Muslim-majority societies, as well as to propose solutions from an Islamic perspective. A descriptive qualitative approach was employed through literature review of Islamic scholars’ thought and contemporary secular trends. The findings indicate that secularism severs the link between knowledge and divine guidance, fosters moral relativism, and undermines the integrity of education. Islam offers the tawhid paradigm, which unites reason and revelation, as both a conceptual and practical solution. The study recommends strategic steps such as revitalizing Islamic education, strengthening the role of scholars, and critically rejecting Western paradigms that conflict with Islamic values. Theoretically, this research contributes to the revitalization of Islamic epistemology, while practically it encourages the reform of Muslim educational institutions.